Kebutuhan Penderita Penyakit Jantung di Usia Dewasa Madya - Dwi Kartika Aulia Putri; Hafizah Putri Salim; Muhammad Haikal; Nurul Azmi Ansari (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Middle adulthood ranges from 40 years to 60 years. The needs of heart disease sufferers in middle adulthood are needs that prioritize physical health such as exercise, diet and regular medication. This research aims to find out how important the needs of individuals suffering from heart disease are. The research method used is a qualitative method with a literature and interview approach. Data was obtained from analysis of related literature as well as in-depth interviews with informants who suffered from heart disease at the age of 58 years. The research results show that the needs of middle adults who suffer from heart disease prioritize health restoration recommended by doctors by means of bypass surgery. This is shown by the improvement in physical health experienced by the informants, by maintaining their diet, taking prescribed medication, exercising regularly, and monitoring their health at recommended clinics. This result has been felt by the informant that changes in his physical condition are currently starting to improve and he is still in the recovery stage.